Development Zones in Asian Borderlands - Eilenberg, Michael, antropoloog, 1975-; Chettri, Mona (Book collections on Project MUSE., 2021)
Development Zones in Asian Borderlands maps the nexus between global capital flows, national economic policies, infrastructural connectivity, migration, and aspirations for modernity in the borderlands of South and South-East Asia. In doing so, it demonstrates how these are transforming borderlands from remote, peripheral backyards to front-yards of economic development and state-building. Development zones encapsulate the networks, institutions, politics and processes specific to enclave development, and offer a new analytical framework for thinking about borderlands; namely, as sites of capital accumulation, territorialisation and socio-spatial changes. Bron: Flaptekst, uitgeversinformatie.